ISLAM DAN DEMOKRASI - Hakim, Lukmanul (Siyasyatuna | Jurnal Hukum Tata Negara, 2025)
This research aims to examine the principles or elements of democracy in the perspective of Islam and the practice of democracy in Islamic governance. This paper also aims to prove the thesis of Samuel Huntington and F. Fukuyama which states that the empirical reality of Islamic society is not compatible with democracy. In normative doctrinal terms, in Islamic teachings there are principles and elements of democracy, although generically and globally. The principles and elements of democracy in Islamic teachings are: as-syura, al-'adalah, al-amanah, al-masuliyyah and al-hurriyyah. The reality of democracy in a country was once applied during the time of the Prophet Muhammad and the khulafaurrasyidin. But after that, most Islamic countries did not inherit these democratic values. This reality does not only occur in Islamic countries, but also non-Islamic countries (the West). Keywords: Democracy from an Islamic Perspective, Democratic Values, Elements of Democracy.